Modelling the competing pathways in the free radical polymerization of acrylates - İnçmen, Mihriban. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
The size of the a-substituent is expected to play a role in the propagation reaction in free radical polymerization. The possibility of the approach of the propagating radical to the monomer can be reduced due to the presence of a bulky group attached to the a carbon atom. It is expected that when the propagating radical is stabilized by some factors, the attack of this radical to the monomer is less favourable compared to the less stable radical. Stability of the radical also affects the termination reactions as well. The presence of an electron donor and an electron withdrawing group causes captodative (cd) effect in radical polymerization. Cd substitution brings about a push-pull resonance stabilization, due to a geminal substitution with both electron-withdrawing and electron-donating groups on the same atom. a-substituted acrylate monomers have been modeled by using the quantum mechanical methods in order to understand the structure reactivity relationship on the propagation and the dispropagation reactions.The propagation and termination rate constants for a-substituted acrylate monomers have been calculated with the B3LYP/6-31+G* methodology. The polymerization kinetics has been considered in order to understand whether correlations between theoretical and experimental findings can be established. The other task of this study is to use the Density Functional Theory (DFT) descriptors in order to understand the cyclopolymerizabilty of diallylic monomers. Density Functional Theory (DFT) descriptors have been used in order to predict the site selectivity in cyclic polymerization.
Keywords: Polymerization.; Acrylates.